Assessing Ecosystem Services in Mangroves: Insights from São Tomé Island (Central Africa) - Afonso, Filipa; Félix, Pedro M.; Chainho, Paula; Heumüller, Joshua A.; de Lima, Ricardo F.; Ribeiro, Filipe; Brito, Ana C. (Frontiers in Environmental Science, 2021)
Mangroves are some of the most productive coastal systems on the planet and provide valuable ecosystem services (ES). They are especially important in threatened ecosystems and developing countries, where they are likely to have direct impacts on local communities. An approach based on ES allows assessing ecosystems across the domains of ecology, sociology and economy. This study focused on the evaluation of ES in mangroves and started by creating a comprehensive global list of mangrove ES based on the Millennium Ecosystem Assessment. These services were then quantified using the best available indicators for mangrove systems. The mangroves of Diogo Nunes, São João dos Angolares and Malanza, located in the São Tomé Island, were used to illustrate the challenges in applying ES indicators in this type of ecosystems. The obtained results confirmed that mangroves can provide important and diverse services. However, the high variability among mangrove systems affects their ability to deliver ES, requiring caution for the extrapolation across regions. This assessment emphasizes how the ES framework can be used as a tool to develop management plans that integrate conservation goals and human wellbeing.